Establishing a framework for visualizing music mood using visual texture - Husain, Adzira; Shiratuddin, Mohd Fairuz; Kok, Wai Wong (2015)
There are many researches that introduce various techniques of browsing and discovering music using “visual forms” to the listeners.“Visual forms” include album cover, colour and mood picture are used to represent music mood in a way that can be easily understood by listeners.It has been proven that visual texture can represent mood too.However there is no research that uses visual texture to represent music mood.In this research, we are proposing a framework for visualising music mood using visual texture.The framework will assist digital music service developers to design visual textures that can represent music mood in a digital music collection application or website. In order to establish the framework, we went through three different stages of the design process.In this paper, we present the three different stages and justify why they are required.